Industrial power engineering and applications handbook - Agrawal, K. C. (Boston : Newnes, 2001)
Never before has so much ground been covered in a single volume reference source. This five-part work is sure to be of great value to students, technicians and practicing engineers as well as equipment designers and manufacturers, and should become their one-stop shop for all information needs in this subject area. This book will be of interest to those working with: Static Drives, Static Controls of Electric Motors, Speed Control of Electric Motors, Soft Starting, Fluid Coupling, Wind Mills, Generators, Painting procedures, Effluent treatment, Electrostatic Painting, Liquid Painting, Instrument Transformers, Core Balanced CTs, CTs, VTs, Current Transformers, Voltage Transformers, Earthquake engineering, Seismic testing, Seismic effects, Cabling, Circuit Breakers, Switching Surges, Insulation Coordination, Surge Protection, Lightning, Over-voltages, Ground Fault Protections, Earthing, Earth fault Protection, Shunt Capacitors, Reactive control, Bus Systems, Bus Duct, & Rising mains *A 5-part guide to all aspects of electrical power engineering *Uniquely comprehensive coverage of all subjects associated with power engineering *A one-stop reference resource for power drives, their controls, power transfer and distribution, reactive controls, protection (including over voltage and surge protection), maintenance and testing electrical engineering.
Part 1: Electric Motors; Part 2: Switchgear Assemblies and Captive Power Generation; Part 3: Voltage Surges, Over voltages and grounding practices; Part 4: Power Capacitators; Part 5: Bus Systems.
Keywords: Factories -- Power supply -- Handbooks, manuals, etc; Electronic books; Handbooks, manuals, etc